Experimental investigation of high-speed melt spinning by means of digital image analysis (2016)
We carry out an experimental characterization via high-speed camera of Chill-Block Melt Spinning process by means of digital optical flow for melt ejection velocity calculation and temperature measurement. © OSA 2016.